Antonina Fedorovna Prikhot’ko (To the centenary of her birthday) (1906–1995) (Физика низких температур, 2006)
The issue in your hands (Low-Temperature Spectroscopy and Optics) is dedicated to the memory of Antonina Fedorovna Prikhot'ko, whose centenary is celebrated by scientific community in 2006.